Propuesta de programa para la prevención de riesgos por desórdenes musculoesqueléticos para los colaboradores de cosecha de yuca de B&C Exportadores en San Carlos - Ruiz-Arguedas, Steven Amed (Instituto Tecnológico de Costa Rica, 2017)
In the present project, a proposal was made for a PROGRAM to PREVENT the risk of musculoskeletal disorders for cassava harvest workers at B & C Exportadores. The methodology used was through the analysis of discomfort, the identification and evaluation of ergonomic risk factors, in the tasks involved in the harvest of cassava, such as starting, tugging, unglapping, placing in baskets, weighing baskets and loading the truck. For the evaluation of the risk factors, the REBA, Strain Index, muscle fatigue analysis and the NIOSH equation were used. When applying these methods, the risk level of the tasks was determined and which of these represented the highest levels, in order to prioritize to apply engineering and administrative controls in the task. The results obtained indicated a very high level of risk for the load task of the truck, followed by this, a high level of risk was detected for basket weighing. The yucca harvesting resulted in a high level of risk due to the postures adopted in this work and the release of a high level of risk due to muscle fatigue for the same work position for a long time. On the other hand, the task with medium risk was that of filling baskets and the task of tijereado presented a low level of risk. It was concluded that the most common ailments are located in the lower back and the hip for the entire study population, which generate interference when working. The implementation of the engineering and administrative controls proposed in the risk prevention program for musculoskeletal disorders, could make the ailments reduce.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Control; Métodos; Antropometría; Procedimientos; Salud; Ergonomía